Pengaruh Kompetensi, Motivasi, Lingkungan Kerja, dan Penggunaan Tehnologi Informasi Terhadap Kinerja Pegawai pada Cabang Dinas Kehutanan Provinsi Jawa Tengah Wilayah X - Intan Prawestri Arum Sari; Bambang Mursito; Sarsono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The Influence of Competence, Motivation, Work Environment, and Information Technology Used on Employee Performance in Cabang Dinas Kehutanan Wilayah X. This research aims to find out the influence of competence, motivation, work environment and Information Technology Used on employee performance simultaneously and partially on employee performance at Cabang Dinas Kehutanan Wilayah X of central java. This research desing the population of all central java is 58 employees. The sampling technique used in this study is a census technique with a sample of 58 employees. Data collection uses questionnaires. Data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and determination coefficient. The research results show that competence, motivation, work environment and the use of information technology on employee performance at Cabang Dinas Kehutanan Wilayah X of Central Java partially and significantly affect the performance of the employees. The suggestions Competence, Motivation, Work Environment, and Information Technology Used at Cabang Dinas Kehutanan Wilayah X of central java will make the performance of employees improve and become better than before.